The negative impact of religious pluralism on the islamic society in Malaysia - Mohamad Zaidin, Mat @ Mohamad (2010)
Religious pluralism is a belief that often gives rise to disputes and debates among various quarters, either for or against the motion. The Islamic society in Malaysia seems to be in a dilemma when it comes to taking a rum stand on this matter. This study intends to discuss and display the facts concerning religious pluralistic beliefs while explaining its danger towards the value of religiosity in Malaysia. The methodology used will be library research and hermeneutic methods. This study concludes that this belief can confuse the beliefs of the muslims and distance them from the true practices of 'Islam. This situation demands lbw all quarters must. play a role in controlling the spread of religious pluralistic beliefs within the society.